Supply Chain Visibility and Social Responsibility: Investigating Consumers’ Behaviors and Motives - Kraft, Tim; Valdés, León; Zheng, Yanchong (Manufacturing and Service Operations Management, 2018)
Consumers increasingly want to know more about where and how the products they purchase are being made. To create transparency requires a company to both gain visibility into its supply chain and disclose information to consumers. In this paper, we focus on the dimension of visibility and investigate when companies can benefit from greater supply chain visibility. To do so, we design an incentivized human–subject experiment to study two key questions: (i) How does supply chain visibility impact consumers’ valuations of a company’s social responsibility (SR) practices in its upstream supply chain? (ii) What roles do indirect reciprocity and consumers’ prosociality play in affecting their valuations under different levels of visibility? In our design, greater visibility is represented by lower uncertainty in the outcomes of a company’s SR efforts. Our results show that consumers value greater visibility regarding a company’s SR practices in the upstream supply chain. This is especially true if consumers exhibit a self-serving bias and use uncertainty as an excuse not to pay for SR. We also observe that high prosocial consumers do not exhibit strong indirect reciprocity. Conversely, indirect reciprocity significantly increases low prosocial consumers’ valuations under High visibility. Our work adds to the experimental literature focusing on transparency and SR (which has primarily studied disclosure) by examining the equally important but understudied dimension of visibility. Furthermore, our results on consumer heterogeneity offer insights into what SR information resonates with a company’s target consumers. The online appendix is available at https://doi.org/10.1287/msom.2017.0685 .